The Bigger Picture: Research Strategy for a Photo-Elicitation Study Investigating Positive Health Perceptions of Older Adults With Low Socioeconomic Status. (17th November 2021) - Platzer, Feline; Steverink, Nardi; Haan, Marieke; de Greef, Mathieu; Goedendorp, Martine
Research focussing on older adults of low socioeconomic status (SES) faces several methodological challenges, including high rates of non-response and drop-out. In addition, older adults of low SES tend to be less willing to participate in research and are more likely to experience cognitive impairments and literacy problems. Photo-elicitation studies do not require high levels of literacy, and they might therefore be suitable for use in research with older adults of low SES. To date, however, little is known about setting up such studies with this target group. Our aim was to demonstrate how we systematically set up a researcher-driven photo-elicitation study to generate greater insight into the positive health perceptions of older adults of low SES. Our strategy consisted of three phases: development, testing and execution. In this article, we discuss each step of the research strategy and describe the limitations and strengths of our study. We also formulate recommendations for further research using photo-elicitation methods with this target group. Based on the results of this study, we conclude that the use of researcher-driven photo-elicitation is a powerful tool for enhancing understanding with regard to positive health perceptions and experiences of older adults of low SES. The usefulness of the method is particularly dependent on the careful development and testing of the study.